2011
DOI: 10.1002/pon.1792
|View full text |Cite
|
Sign up to set email alerts
|

The experiences, needs and concerns of younger women with breast cancer: a meta‐ethnography

Abstract: Objective: This meta-ethnography synthesises the evidence on the experiences, needs and concerns of younger women with breast cancer.Methods: Using a method called 'reciprocal translation' we developed a conceptual model to reflect the local and social contexts, issues, processes, needs and concerns of importance in this literature.Findings: Key findings relate to the particular point in the life-course at which young women with breast cancer stand. Issues for these women relate to feeling different as a resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
1
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 31 publications
(111 reference statements)
5
66
1
7
Order By: Relevance
“…A recent literature synthesis on the experiences, needs and concerns of younger women with breast cancer reported underdeveloped social support networks and concerns regarding reproduction, fertility and sexuality (Adams, McCann, Armes, Richardson, Stark, Watson et al 2011). Younger women have to balance their own needs against the needs of their family, trying to protect children from the impact of the cancer and meet the financial demands of the household by maintaining paid employment (Adams, McCann, Armes, Richardson, Stark, Watson et al 2011). These age related issues were at the fore for participants in the current study.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…A recent literature synthesis on the experiences, needs and concerns of younger women with breast cancer reported underdeveloped social support networks and concerns regarding reproduction, fertility and sexuality (Adams, McCann, Armes, Richardson, Stark, Watson et al 2011). Younger women have to balance their own needs against the needs of their family, trying to protect children from the impact of the cancer and meet the financial demands of the household by maintaining paid employment (Adams, McCann, Armes, Richardson, Stark, Watson et al 2011). These age related issues were at the fore for participants in the current study.…”
Section: Discussionmentioning
confidence: 82%
“…It has been reported that younger women with breast cancer experience higher levels of distress, are more likely to be depressed and cope less well than older women (Cimprich, Ronis, Martinez-Ramos 2002;). A recent literature synthesis on the experiences, needs and concerns of younger women with breast cancer reported underdeveloped social support networks and concerns regarding reproduction, fertility and sexuality (Adams, McCann, Armes, Richardson, Stark, Watson et al 2011). Younger women have to balance their own needs against the needs of their family, trying to protect children from the impact of the cancer and meet the financial demands of the household by maintaining paid employment (Adams, McCann, Armes, Richardson, Stark, Watson et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies investigating the survivorship experience of young BCS have used a similar age cut-off [24]. The following eligibility criteria were used: participants were required to: have the ability to read and comprehend English and be over 18 years of age.…”
Section: Participantsmentioning
confidence: 99%
“…Having a diagnosis under the age of 45 is not a universal age cut-off for a 'young' breast cancer diagnosis. But studies have shown that 45 is an appropriate age to choose because it is inclusive of young BCS with dependent children living at home [24].…”
Section: Limitationsmentioning
confidence: 99%
“…Given the paucity of research into the requirements of this young population group 19,20 , studies are greatly needed to characterize this vulnerable population, particularly those living in socioeconomic disadvantage marked by little access to health care. In this manuscript, we aim to analytically explore existing knowledge regarding the needs of YWBC in LMICs to provide a better understanding of their specific requirements and to guide the future targeted strategies for healthcare providers in limited resource settings.…”
Section: Context: Countries With Limited Resourcesmentioning
confidence: 99%